Impact of seasonal temperature shift on leaf senescence physiology and structure of Dalbergia sissoo Roxb. under semiarid conditions - Muhammad Shareef; Waleed Hussain; Fanjiang Zeng; Fatiha Shakeel; Saira Boota; Bo Zhang (Flora, 2026)

Hydrological perspective of landslide dams: a review - Muhammad Shareef Shazil; Thom Bogaard; Roberto Greco (Natural Hazards, 2026)
Landslide dams, created when rapid mass movements block river channels, are strongly influenced by hydrological conditions of the upstream catchment. The formation and long-term stability of landslide dams are closely linked to hydrological factors such as streamflow, lake area, water level and precipitation. Conversely, the formation of these dams changes upstream and downstream hydrological regimes such as water storage, sediment transport and flooding risk. Since the previous reviews by Costa and Schuster, (1988) and Korup, (2002), several review articles have focused on the formation and failure mechanism of landslide dams (e.g., Fan et al. 2020; Zheng et al. 2021). These reviews have mainly focused on geomorphological factors of dams and their formation. However, the hydrological processes around and within the landslide dam are crucial for the behavior of landslide dams, the downstream hydrology and potential flash flood risks. Therefore, there is an urgent need to study hydrological processes upstream and within landslide dams in order to better predict landslide dam stability, up- and downstream consequences. Streamflow (inflow and outflow), precipitation and snowmelt, water level, dammed lake area, lake volume, water balance, surface runoff, erosion, sedimentation, and water storage capacity are key factors for assessing the behavior of landslide dams. This review analyzes the current state of knowledge on hydrological processes influencing the evolution, and failure of landslide dams. It further examines the role of remote sensing and modelling techniques in assessing hydrological factors where field data are scarce.

The Evolution of Organoids: From Discovery to Cutting-Edge Applications - Javeria Umber; Uzair Ahmed; Tazeem Fatima; Muhammad Qasim; Usman Ali Ashfaq; Muhammad Shareef Masoud (Stem Cell Reviews and Reports, 2026)

Hydrothermal synthesis of novel Mn3O4-Nd2O4 nano-hybrid as bi-functional electrocatalyst for water splitting - Muhammad Ibrar; Iram Manzoor; Mostafa A. Ismail; Misbah Shareef; Habiba Batool; Sana Ben Khalifa; Saleh Chebaane; Zeineb Klai (Fuel, 2026)

Genome-wide identification and expression analysis of YTH gene family in barley reveals their potential role under abiotic stresses - Muhammad Mudasir; Muhammad Shahzad; Ayesha Bibi; Shareef Gul; Liu Qiuyi; Sarmad Frogh Arshad; Hameed Gul; Ali Shahzad (Genetica, 2026)

Exosomal CeRNAs from the tumor microenvironment: hidden drivers of colorectal cancer progression - Faris Anad Muhammad; Abdulkareem Shareef; S. Renuka Jyothi; Priya Priyadarshini Nayak; J. Bethanney Janney; Gurjant Singh; Aashna Sinha; Nodira Rabbimova; Hayder Naji Sameer; Ahmed Yaseen; Rasim M. Salih; Mohaned Adil (Journal of Molecular Histology, 2026)

Macrophage migration inhibitory factor (MIF): a Janus-faced cytokine in viral pathogenesis and host defense - Mohamed J. Saadh; Faris Anad Muhammad; Abdulkareem Shareef; S. Renuka Jyothi; Priya Priyadarshini Nayak; Ashish Singh Chauhan; Siya Singla; Farida Khasanjanova; Hayder Naji Sameer; Ahmed Yaseen; Zainab H. Athab; Mohaned Adil (Immunologic Research, 2025)

From roots to resilience: Strigolactones for boosting crop resilience and productivity under stressful environments - Zeeshan Ahmed; Dongwei Gui; Ghulam Murtaza; Muhammad Shareef; Akash Tariq (Journal of Environmental Management, 2025)

N-acetylcysteine as a feed additive to counteract ochratoxin A toxicity in poultry - Muntaha Tanveer; Muhammad Imran; Muhammad Kashif Saleemi; Mubashar Shareef; Muhammad Imran; Saqib Umar (Food Additives & Contaminants: Part A, 2025)

Synthesis, biological evaluation, and in silico studies of chalcone-based ketamine derivatives with preferential COX-2 inhibitory activity - Syed Muzzammil Masaud; Humaira Nadeem; Abida Shamim; Muhammad Kazim Zargaham; Usman Shareef; Sana Ayaz; Babar Murtaza (Medicinal Chemistry Research, 2025)

Comparative Genetic Analysis of Triticum aestivum Varieties Under Salt Stress: Integrating Morphological and Biochemical Traits - Shareef Gul; Hameed Gul; Muhammad Mudasir; Maroof Fatima; Hesheng Yao; Ali Shahzad (Journal of Crop Health, 2025)

Harnessing the Duo Effect of Plant Growth-Promoting Rhizobacteria and Organic Amendments in the Phytoremediation of Cadmium: a Review - Muhammad Junaid Sarwar; Muhammad Shabaan; Muhaimen Ayyub; Zahir Ahmad Zahir; Hafiz Naeem Asghar; Kashiuf Asif; Aqsa Shareef; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2025)

Recovery Efficacy of Differentially Applied Nitrogen Regulates the Metabolism Coupled Physiological Phenotyping of Cotton on Leaching Prone Sandy Soil of Desert - Muhammad Shareef; Fanjiang Zeng; Gui Dongwei; Zeeshan Ahmed; Muhammad Waqas; Hassan Iqbal; Bo Zhang; Muhammad Waseem (Journal of Soil Science and Plant Nutrition, 2024)

Spatio-temporal analysis of hydrometeorological variables for terrestrial and groundwater storage assessment - Muhammad Shareef Shazil; Sheharyar Ahmad; Syed Amer Mahmood; Syed Ali Asad Naqvi; Sanju Purohit; Aqil Tariq (Groundwater for Sustainable Development, 2024)

Urbanization-led land cover change impacts terrestrial carbon storage capacity: A high-resolution remote sensing-based nation-wide assessment in Pakistan (1990–2020) - Mirza Waleed; Muhammad Sajjad; Muhammad Shareef Shazil (Environmental Impact Assessment Review, 2024)

Genome wide identification and expression profiling of PYL genes in barley - Ali Shahzad; Muhammad Shahzad; Muhammad Imran; Hameed Gul; Shareef Gul (Plant Gene, 2023)

Systematic elucidation of the multi-target pharmacological mechanism of Terminalia arjuna against congestive cardiac failure via network pharmacology and molecular modelling approaches - Aqsa Asghar; Muhammad Qasim; Fatima Noor; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Shareef Masoud; Rashid Bhatti; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem (Natural Product Research, 2023)

An investigation into the critical tension of electroporation in anionic lipid vesicles - Mohammad Abu Sayem Karal; Md. Kabir Ahamed; Urbi Shyamolima Orchi; Md. Towhiduzzaman; Marzuk Ahmed; Shareef Ahammed; Nadia Akter Mokta; Muhammad Samir Ullah (European Biophysics Journal, 2021)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Impact of drought on assimilates partitioning associated fruiting physiognomies and yield quality attributes of desert grown cotton - Muhammad Shareef; Dongwei Gui; Fanjiang Zeng; Zeeshan Ahmed; Muhammad Waqas; Bo Zhang; Hassan Iqbal; Muhammad Fiaz (Acta Physiologiae Plantarum, 2018)

Assessment of seasonal variation for air pollutant accumulation by Zizyphus tree under washing treatment - Mohamed Abdulraheem Shaheen; Fathy Saad El-Nakhlawy; Fahd Mosallam Almehmadi; Muhammad Zahid Ihsan; Abdulmohsin Rajeh Al-Shareef (Environmental Monitoring and Assessment, 2016)